Investment Strategy in the Banking Sector: Probability Ratio Analysis and Comparison of Financial Performance in Core Bank Group 4 (BCA, BRI, BNI, Mandiri) - Wardoyo, Chess Satriya; Suryadi, Joanes Ferdienand (International Journal of Global Operations Research, 2025)
This study aims to analyze performance bank finances in KBMI group 4 (Bank BCA, BRI, BNI, and Mandiri ) with a focus on the ratio profitability as a foundation taking decision investment . Using the method descriptive comparatively , this study analyzes financial data in five year period Lastly , with a focus on the Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Cost of Goods (Cash) indicators . Operational to Income Operational (BOPO). Research results show that there is difference significant in profile profitability the four banks, with BCA showing consistency highest in profitability and efficiency operational . BRI shows superiority in NIM, while Mandiri and BNI show improvement stable performance . Investment strategy model formulated based on analysis risk -return, cycle economy , and trends industry banking . This research provides different investment strategy recommendations based on profile investor risk , taking into account special to impact digital transformation and change regulation in the sector Indonesian banking .